THE HYDROTHERMAL ALKALI METASOMATISM EFFECTS ON GRANITIC ROCKS: QUARTZ DISSOLUTION AND RELATED SUBSOLIDUS CHANGES - Cathelineau Michel (My University, 1986)
The hydrothermal leaching of quartz from granite is frequently associated with sodium and/or potassium metasomatism, which promotes important alterations in the primary mineralogy, together with concomitant changes in the whole-rock composition. The differential stability of granite minerals other than quartz during alteration, and the variety of vug infillings, explains the range of the observed chemical changes. Theoretical chemical compositions and parameters may be calculated from the mineral parageneses. Thus, by comparing theoretical and natural trends in chemical mineralogical diagrams it is possible to define and to classify major alteration processes. The P-T conditions during metasomatism range from 0?3 to 1?5 kb, and from 250 to 450°C. The metasomatic fluids are aqueous and of low salinity. Alteration results from a series of disequilibrium reactions between fluids and host rocks. Undersaturation of quartz in the fluids results from drastic temperature changes in the range 450-350°C, and in most cases the K or Na metasomatism is controlled by the subsequent disequilibrium between fluids and host rocks.